2024
DOI: 10.3389/fped.2024.1334221
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based mindfulness programs using virtual reality to reduce pediatric perioperative anxiety: a narrative review

Brandon Benchimol-Elkaim,
Bassam Khoury,
Argerie Tsimicalis

Abstract: Over 75% of pediatric surgery patients experience preoperative anxiety, which can lead to complicated recoveries. Current interventions are less effective for children over 12 years old. New interventions, like mindfulness-based ones (MBIs), are needed to address this issue. MBIs work well for reducing mental health symptoms in youth, but they can be challenging for beginners. Virtual reality (VR) nature settings can help bridge this gap, providing an engaging 3-D practice environment that minimizes distractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Those met the following criteria were excluded: (1) with a history of mental and psychological disorders or a family history of mental illness; (2) unable to communicate with the investigators; (3) critical illness, emergency operation; (4) combined with severe metabolic diseases; (5) combined with congenital self-care disorder; (6) with developmental abnormalities or congenital malformations.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Those met the following criteria were excluded: (1) with a history of mental and psychological disorders or a family history of mental illness; (2) unable to communicate with the investigators; (3) critical illness, emergency operation; (4) combined with severe metabolic diseases; (5) combined with congenital self-care disorder; (6) with developmental abnormalities or congenital malformations.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…An international study has shown that more than 75% of pediatric patients have anxiety before surgery [4]. Studies have shown that preoperative interventions, such as preoperative games, virtual reality technology, and robot companion, are beneficial to alleviate children's preoperative anxiety, which has become a standard procedure in developed countries in Europe and the United States [5][6][7]. Moreover, developed countries generally adopt a more comprehensive approach to psychological care, including a child-friendly medical environment, professional psychological counseling for children, and active communication with children and their parents.…”
Section: Introductionmentioning
confidence: 99%